Basaloid squamous cell carcinoma of the head and neck: role of HPV and implication in treatment and prognosis. Issue 10 (27th September 2010) - Thariat, J; Badoual, C; Faure, C; Butori, C; Marcy, P Y; Righini, C A
Abstract : Basaloid squamous cell carcinoma (BSCC) is a rare variant of squamous cell carcinoma (SCC) of the head and neck. Wain's criteria (peripheral palisading, association with SCC, high nuclear-cytoplasmic ratio, high mitotic rate, solid growth), anti-34BE12 and CK 5/6 staining, and absence of neuroendocrine markers are mandatory for the diagnosis of BSCC. Its increasing incidence parallels that of human papilloma virus (HPV)-positive tumours for the oropharyngeal subsite. On the other hand, BSCC is frequently considered a high-grade carcinoma of poorer prognosis than its SCC counterparts, mostly due to a higher rate of distant metastases. However, BSCC has similar or better locoregional control rates and a relatively better radiosensitivity than SCC. BSCC seems to have a dual behaviour depending, at least partly, on its recently described association with HPV. The basaloid subtype of SCC, owing to its particular behaviour, should be systematically investigated along with HPV and smoking status, as those factors may be determinant in the response to treatment.